Identifying key parent-reported symptoms for detecting depression in high risk adolescents. (30th August 2016) - Thapar, Ajay K.; Hood, Kerenza; Collishaw, Stephan; Hammerton, Gemma; Mars, Becky; Sellers, Ruth; Potter, Robert; Craddock, Nick; Thapar, Anita; Rice, Frances
Abstract: Adolescent offspring of depressed parents are at particularly heightened risk of developing early onset Major Depressive Disorder (MDD) yet are unlikely to access services. We therefore aimed to identify a parsimonious combination of parent-reported symptoms that accurately detected offspring MDD. We used a multi-sample study comprising a development sample of 335 offspring of adults with recurrent MDD assessed on three occasions (mean age 12.4–14.8 years) and an independent validation sub-sample of 807 adolescents from a general population cohort (mean age 13.1 years). Parent ratings of psychiatric symptoms in adolescent offspring were assessed using established questionnaires. The best performing four-item combination of symptoms was identified. Accuracy in detecting concurrent DSM-IV MDD diagnosis, assessed by direct adolescent and parent interviews, was compared to the well-established 13-item short Moods and Feelings Questionnaire (sMFQ) using ROC curve analysis. The combination identified (concentration problems, anhedonia, worrying excessively and feeling unloved) performed equivalently to the sMFQ both in the development dataset and in the validation dataset. We concluded that a combination of four parent-reported mental health items performs equivalently to an established, longer depression questionnaire measure in detecting a diagnosis of adolescent major depressive disorder among offspring of parents with recurrent MDD and needs further evaluation. Highlights: Adolescent offspring of adults with recurrent MDD are a high-risk group. Do specific parent-reported items detect adolescent MDD?. Yes-anhedonia, concentration problems, worrying excessively and feeling unloved. If ≥ 2 symptoms reported, MDD detection accuracy similar to a longer measure. If <2 symptoms reported, MDD highly unlikely to be present.